Validasi Media Pembelajaran Menulis Cerpen Berbasis Web Kultural - Agnes Apryliana; Hany Uswatun Nisa (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2021)
This study aims to describe the validity of learning media to write short stories. The research method used is descriptive qualitative. The results of this study indicate that the learning media developed are feasible and effective for use in the learning process. The feasibility is seen from the assessment of material, media, and media users' responses with a mean score of 81.25% and in the "good" category so that the higher the average score obtained, the better the validity of the product. In conclusion, learning media that are made specifically for writing short story materials based on cultural web are categorized as good and can be used thoroughly during short story writing learning. Keywords: Short stories, Web, Validation